Concentrations of preptin, salusins and hepcidins in plasma and milk of lactating women with or without gestational diabetes mellitus - Aydin, Suleyman; Celik, Onder; Gurates, Bilgin; Sahin, Ibrahim; Ulas, Mustafa; Yilmaz, Musa; Kumru, Selahattin (Elsevier Science Inc, 2013)
This study was undertaken to ascertain whether human milk contains preptin, salusin-alpha (salusin-alpha) and -beta (salusin-beta) and pro-hepcidin and hepcidin-25, and whether there are relationships between plasma and milk preptin, salusin-alpha and -beta and pro-hepcidin and hepcidin-25 concentrations in lactating mothers with and without gestational diabetes mellitus (GDM). Blood was obtained from non-lactating women (n = 12), non-diabetic lactating women (n = 12), and GDM lactating women ( n = 12). Colostrum, transitional milk, and mature milk samples were collected just before suckling from healthy and GDM lactating women. Peptides concentrations were determined by ELISA and EIA. Mammary gland tissues were screened immunohistochemically for these peptides. Women with GDM had significantly higher plasma and colostum preptin concentrations than healthy lactating women during the colostral and transitional milk period. Salusin-alpha and -beta levels in milk and plasma were lower in women with GDM. Salusin-alpha and -beta were significantly lower in both plasma and colostrums of GDM than of healthy lactating women. Women with GDM had significantly higher colostum pro-hepcidin and hepcidin-25 concentrations than healthy lactating women during the colostral period. Plasma prohepcidin was also higher in women with GDM than in healthy lactating women during the colostral period, but plasma prohepcidin and hepcidin-25 levels decreased during mature milk period. Transitional milk pro-hepcidin and hepcidin-25 levels in women with GDM were higher than in healthy lactating women. All these results revealed that the mammary gland produces those peptides, which were present in milk at levels correlating with plasma concentrations. (C) 2013 Elsevier Inc. All rights reserved.
Keywords: Preptin; Salusin; Hepcidin; Gestational diabetes mellitus